2012
DOI: 10.31258/jnat.14.1.37-41
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme–Catalysed Synthesis of Palm-Based Wax Esters-A Kinetic Study

Abstract: Wax esters are long chain esters that are derived from fatty acids and alcohols with chain lengths of 12 carbons or more. Wax esters have a wide range of application in industrial especially in cosmetics. The present work focuses on the synthesis of wax esters by alcoholysis reaction from palm oil and oleyl alcohol in hexane by lipase from Rhizomucor meihei (Lipozyme IM). Effect of various concentrations of palm oil and oleyl alcohol were studied to deduce the kinetics and mechanism of the reaction. The alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…One of the sources of non-edible materials that availability is abundant and can be converted into FAME is cotton seed oil. Previous studies showed that the oil content of kapok seed is 30.075%, (Asnawati et al, 2014) The synthesized FAME from the oils can be synthesized using chemicals and enzymatic catalyzed methods (Gunawan et al, 2011). The latter method is known to be expensive, however it provides advantages that the former cannot give.…”
Section: Famementioning
confidence: 99%
“…One of the sources of non-edible materials that availability is abundant and can be converted into FAME is cotton seed oil. Previous studies showed that the oil content of kapok seed is 30.075%, (Asnawati et al, 2014) The synthesized FAME from the oils can be synthesized using chemicals and enzymatic catalyzed methods (Gunawan et al, 2011). The latter method is known to be expensive, however it provides advantages that the former cannot give.…”
Section: Famementioning
confidence: 99%
“…Persen hasil asam lemak etanolamida maksimum pada konsentrasi etanolamina 20,10 mmol dengan jumlah enzim 0,16 g. Hal ini disebabkan karena semakin tinggi konsentrasi substrat, maka semakin banyak pula jumlah molekul substrat yang bersaing untuk menempel pada sisi aktif permukaan enzim [10]. Akan tetapi, pada konsentrasi substrat di atas 20,10 mmol tidak terjadi peningkatan persen hasil asam lemak etanolamida, hal ini disebabkan karena jumlah enzim tidak mampu menyaingi jumlah substrat yang bertambah dan tidak akan meningkatkan persen hasil secara signifikan [30]. Jika adanya penambahan jumlah enzim, maka enzim dapat mengkatalisis substrat lebih cepat dan maksimal.…”
Section: Interaksi Antar Variabel Aunclassified